Role of pH on the structure, composition and morphology of C-S-H–PCE nanocomposites and their effect on early strength development of Portland cement. (December 2017) - Kanchanason, V.; Plank, J.
Abstract: Synthetic C-S-H–PCE nanocomposites are known to act as seeding material in Portland cement. Here, C-S-H–PCE was precipitated from Na2 SiO3 and Ca(NO3 )2 solutions in an isoprenolether (IPEG)-based PCE solution at pH values of 10.4, 11.7, 12.4 and 13.8. It was found that at pH = 10.4 the C-S-H–PCE precipitate is amorphous, possesses a disordered structure, consists of partially branched silicate chains and exhibits a globular morphology. At pH = 11.7, the precipitate is semi-crystalline and consists of shorter, non-branched silicate chains. Moreover, it contains the highest amount of ultra-small nanofoils (< 50 nm) and can sorb the largest amount of PCE (~ 250 mg/g C-S-H). It shows optimal seeding effect in cement when compared with globular or foils of C-S-H–PCE exhibiting larger size (> 200 nm) obtained at pH = 12.4 and 13.8, respectively.